Historical aspects of printing and publishing in languages of the Middle East: papers from the Third Symposium on the History and Printing and Publishing in the Languages and Countries of the Middle East, University of Leipzig, September 2008 - Roper, Geoffrey (Islamic manuscripts and books, 2014)
Mediaeval Arabic block printing : state of the field / Karl Schaefer -- Fruher Druck mit arabischen Typen in Leipzig, 17.-18. Jahrhundert / Boris Liebrenz -- Enlightenment in the Ottoman context : Ibrahim Muteferrika and his intellectual landscape / Vefa Erginbas -- Waiting for Godot : the formation of Ottoman print culture / Orlin Sabev (Orhan Salih) -- Printing and the abuse of texts in al-Gabarti's History of Egypt / Sarah Mirza -- Judaeo-Arabic printing in North Africa, 1850-1950 / Yosef Tobi -- Marginal miniatures : the Tehran edition of al-Damiri's Hayat al-hayawan (1285/1868) / Ulrich Marzolph -- The establishment of the Syrian Orthodox Patriarchate press / Ahmet Tasgin and Robert Langer -- L'Imprimerie Ebuzziya et l'art d'imprimer dans l'Empire Ottoman a la fin du XIXe siecle / Ozgur Turesay -- A champion of printing quality in the Ottoman Turkish press of the Second Constitutional period : Sehbal journal / Bora Ataman and Cem Pekman -- Arabic and bilingual newspapers and magazines in Latin America and the Caribbean / Philipp Bruckmayr -- A short history of Kurdish publishing and prospects for its future / Blair Kuntz -- The Bulaq Press Museum at the Bibliotheca Alexandrina / Ahmed Mansour.